2018
DOI: 10.1007/s42452-018-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of amine terminated polyether shale inhibitor for water-based drilling fluid

Abstract: Facing the problems of shale hydration, swelling and borehole wall instability in shale gas drilling, a new type of amine terminated polyether (ATPE) shale inhibitor used in water-based drilling fluid is successfully synthesized through the method of leaving group. Using the yield of ATPE as index, orthogonal experiments are designed to determine the optimal reaction conditions. When the mole ratio of polyethylene glycol tosylate (PEG-OTs)/ethylenediamine is 1/3.6, mole ratio of PEG-OTs/triethylamine (acid bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…The spectra of P8k (Figure 6) showed chemical shift was around 3.7 ppm for the methene (−CH 2 −) protons of PEG chains. 66,67 The resonance peak, centered at 3.705 ppm at 5 mg/mL concentration, shifted gradually with increase in concentration, and appeared at 3.721 ppm at concentration of 200 mg/mL. This remarkable shift toward higher chemical shift constitutes a solid support that the electron density around the ethylene protons was decreasing with increased PEG concentration, owing to likely the electron clouds shifting around C−H bonds toward the ether O atoms (C−O−C), because the increased sharing or through-space conjugation of the electrons, due to the cluster formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The spectra of P8k (Figure 6) showed chemical shift was around 3.7 ppm for the methene (−CH 2 −) protons of PEG chains. 66,67 The resonance peak, centered at 3.705 ppm at 5 mg/mL concentration, shifted gradually with increase in concentration, and appeared at 3.721 ppm at concentration of 200 mg/mL. This remarkable shift toward higher chemical shift constitutes a solid support that the electron density around the ethylene protons was decreasing with increased PEG concentration, owing to likely the electron clouds shifting around C−H bonds toward the ether O atoms (C−O−C), because the increased sharing or through-space conjugation of the electrons, due to the cluster formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It revealed that β‐CD‐HBP‐OH was not a proper inhibitor for crystalline hydration due to its larger molecular size. Although some inorganic salt inhibitors and linear polymer inhibitors were reported to decrease the interlayer spacing d 001 of wet bentonite for restricting crystalline hydration, it seemed that the molecular weight of hyperbranched polymer dominated the inhibition interaction types. Greater molecular weight meaned larger molecular size with more terminal groups.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is essential to inhibit the hydration and dispersion of shale in the drilling process. In recent decades, literature reports that KCl, CaCl 2 , nanoparticles, ionic liquid, cellulose derivative, polyethyleneimine, polyoxyalkyleneamine, amine‐terminated polymer, polyols and nonionic molecules/polymers have been acted as inhibitors for shale hydration. Among them, amine‐terminated inhibitors are attractive due to their high performance with low dosage.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51][52][53] Other functional monomers such as N,N-diallylbenzylamine, 47 styrene, 48 and N-vinylpyrrolidone 49 have improved the thermal stability and chemical stability of final copolymers. From another perspective, primary amine, [55][56][57] and quaternary ammonium 44,50,51 have been main inhibitory groups for decades, and it is innovative to develop novel functional groups to inhibit bentonite hydration.…”
Section: Introductionmentioning
confidence: 99%